Challenging treatment of hidradenitis suppurativa with happy ending - Akici, Murat; Cilekar, Murat (International Surgery Journal, 2019)
Background: Hydradenitis supurativa (HS) is a chronic, recurrent and inflammatory disease which involves skin and subcutaneous fatty tissue. The aim of this study was to retrospectively evaluate the treatment results of 12 patients who were diagnosed as hidradenitis suppurativa with local or multiple site involvements in our clinic. Methods: Data of 12 patients with local or multiple site involvement, who had hidradenitis suppurativa surgery between January 2013 and January 2018 were evaluated retrospectively. Results: Twelve patients, who were male, were included in the study. The average age was 39.4 (25-56) years old. A total of 5 patients were with local and 7 patients were with multiple region involvements. 8 patients had axillary, 3 patients had genitalia, 4 patients had perianal and 7 patients had sacral region involvements. Two of 4 patients with perianal region had protective stomas. In total, 16 surgical procedures were performed to the patients. In 6 patients, some parts of wounds were primary closed and followed-up with secondary healing. Skin grafting was performed for the four of these patients in late period. In 4 patients, defects were closed with primary closure and with rotation flaps in 2 patients. No recurrence was observed among the patients. The average duration of follow-up was 32.5 months. Conclusions: The surgical treatment process of hidradenitis suppurativa, which is a chronic disease, is not more difficult and longer than its natural course. In recent years, complete recovery can be achieved with current surgical methods.